1992
DOI: 10.1002/1097-0142(19921201)70:11<2713::aid-cncr2820701124>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic adaptation of survivors of childhood cancer

Abstract: When adult survivors of childhood cancer were compared with their peers, survivors were found to be at least as well adjusted. Indeed, some evidence was suggestive of survivors having adaptive advantages in everyday life. The survivors reported significantly more positive affect, less negative affect, higher intimacy motivation, more perceived personal control, and greater satisfaction with control in life situations. Despite these apparent strengths associated with surviving childhood cancer, several specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 40 publications
7
93
0
3
Order By: Relevance
“…See Table III for a presentation of results in studies with a comparative design with regard to this theme. A more positive attitude towards the family [43], a preference for interacting with others [31], more positive emotions when interacting with others [31], better social relationships [43], and less anti-social behaviour [63] than for comparison groups were expressed by self-reports. Teachers reported less aggressive and disruptive behaviour for survivors than for a comparison group [65].…”
Section: Relations To Otherssupporting
confidence: 89%
See 1 more Smart Citation
“…See Table III for a presentation of results in studies with a comparative design with regard to this theme. A more positive attitude towards the family [43], a preference for interacting with others [31], more positive emotions when interacting with others [31], better social relationships [43], and less anti-social behaviour [63] than for comparison groups were expressed by self-reports. Teachers reported less aggressive and disruptive behaviour for survivors than for a comparison group [65].…”
Section: Relations To Otherssupporting
confidence: 89%
“…When treatment ends, those struck by childhood cancer may experience a profound need to socialise with others in their striving to achieve a normal life. This may explain why survivors report a preference for interacting with others [31] and more positive emotions when interacting with others [31] than comparison groups. Trying to fit in with their former social life, survivors may be eager to present themselves favourably [42], and may exhibit less antisocial [63], aggressive and disruptive behaviour [65] than comparison groups.…”
Section: Discussionmentioning
confidence: 99%
“…siblings) (Stam et al, 2006;Reinfjell et al, 2009;Zeltzer et al, 2009). However, most studies found that on the whole, survivors of childhood cancer fare the same or have a good QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and function well psychologically (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008). Yet, only a few studies had reported results by both parent proxy and adolescent self-report, compared with controls.…”
Section: Quality Of Lifementioning
confidence: 99%
“…However, we cannot rule out the consequences of long-term psychological strain because of the effects of the cancer disease and its treatment. In various studies suggesting that childhood cancer survivors function well psychologically (Zeltzer et al, 2009;Gray et al, 1992;Langeveld et al, 2002) despite a seemingly traumatic childhood experience, it was unclear if survivors were suffering from late effects or not. Taken into consideration, these findings may support the suggestion of a biological and psychological source for a poorer QoL experience among children who have survived cancer.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation